Inorganic matter in-situ modified polyimide nanofiber and modified composite diaphragm

By depositing inorganic substances in situ on the surface of polyimide nanofibers to form a modified composite separator, the problem of polyolefin separator shrinkage at high temperature is solved, the safety and high temperature resistance of the battery are improved, and more stable ceramics are achieved Coated structure.

CN119162696APending Publication Date: 2024-12-20ZHEJIANG OCAS NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411119944.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Commercial polyolefin separators are prone to large-area shrinkage at high temperatures, resulting in short circuit or thermal runaway inside the battery. Existing improvement measures such as coating inorganic ceramic particles still cannot meet the requirements of high safety.

Method used

Using inorganic in situ modified polyimide nanofibers and modified composite separators, the ceramic coating is formed by depositing inorganic precursor salts on the fiber surface, electrospinning and imidizing treatment, and the ceramic is improved. Compatibility and integrity of particles can avoid powdering problems caused by adhesive failure and form a stable network structure.

Benefits of technology

It significantly improves the safety and high temperature resistance of the battery, avoids the thermal melting of the polyolefin-based film at high temperatures, and enhances the integrity of the ceramic coating and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162696A_ABST
    Figure CN119162696A_ABST
Patent Text Reader

Abstract

The invention provides an inorganic matter in-situ modified polyimide nanofiber and a modified composite diaphragm, and the nanofiber is prepared by the following method: carrying out polycondensation on monomers of aromatic dianhydride and aromatic diamine to obtain a polyamide acid spinning solution, adding an inorganic matter precursor salt solution, uniformly mixing, carrying out electrostatic spinning, and carrying out imidization treatment to obtain the inorganic matter in-situ modified polyimide nanofiber. The nanofiber is obtained. Inorganic matter is deposited on the surface of the fiber in situ, so that the in-situ modified polyimide nanofiber is obtained, the high-temperature resistance of the nanofiber can be further improved, the compatibility of the nanofiber and inorganic ceramic particles can be improved, the integrity of a ceramic coating in the modified composite diaphragm is improved, and the service life of the composite diaphragm is prolonged. The problem of pulverization of unmodified polyimide nanofibers caused by failure of an adhesive is avoided, meanwhile, a stable network structure is formed, hot melting of the polyolefin base membrane at high temperature is avoided, and the safety of the battery is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery separators, and in particular to an inorganic in-situ modified polyimide nanofiber and a modified composite separator. Background Art

[0002] Lithium-ion battery is a green high-energy power source with advantages such as extremely high energy density, relatively long cycle life, and fast charge and discharge. With the continuous improvement of the preparation process, its production cost is also continuously reduced. Lithium-ion battery separator is one of the key components inside lithium-ion battery. It can not only separate the positive and negative electrodes of the battery, but also provide microporous channels for the exchange of lithium ions between the positive and negative electrodes. Therefore, a separator with excellent performance can have a great impact on the comprehensive performance of the battery.

[0003] At present, the melting point of commercial polyolefin separators is only 130-170℃, which is prone to large-area shrinkage at high temperatures, leading to internal short circuits or thermal runaway of the battery, and urgently needs to be improved. To this end, people coat the surface of polyolefin separators with a layer of high-temperature resistant inorganic ceramic particles such as silicon dioxide SiO2 and aluminum oxide A12O3, which improves the thermal stability of the separator, but still cannot meet the high safety requirements. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes an inorganic in-situ modified polyimide nanofiber and a modified composite diaphragm, and utilizes the in-situ deposition of inorganic matter on the fiber surface to obtain an in-situ modified polyimide nanofiber, which can not only further improve the high temperature resistance of the nanofiber, but also improve the compatibility of the nanofiber and the inorganic ceramic particles, increase the integrity of the ceramic coating in the modified composite diaphragm, avoid the pulverization problem of the unmodified polyimide nanofiber due to the failure of the adhesive, and at the same time form a stable network structure to avoid the thermal melting of the polyolefin base film at high temperature, thereby greatly improving the safety of the battery.

[0005] The present invention provides an inorganic in-situ modified polyimide nanofiber, wherein the nanofiber is prepared by the following method:

[0006] S1, polycondensing the monomers of aromatic dianhydride and aromatic diamine to obtain a polyamic acid spinning solution;

[0007] S2, adding the inorganic precursor salt solution to the polyamic acid spinning stock solution, mixing, and obtaining precursor fibers after electrospinning;

[0008] S3, subjecting the precursor fiber to imidization treatment to obtain the inorganic in-situ modified polyimide nanofiber.

[0009] In the present invention, an inorganic precursor salt is added to the electrospinning stock solution of polyimide, and after electrospinning and imidization, an inorganic in-situ modified polyimide nanofiber is obtained; here, considering that polyimide is a high-performance polymer material integrating excellent mechanical properties, high and low temperature resistance, dielectric properties, wear resistance, ultraviolet radiation resistance, chemical and dimensional stability, the polyimide nanofiber prepared by electrospinning combines the advantages of polyimide material and electrospinning, and has the advantages of excellent high temperature resistance, high porosity and flexibility; and by in-situ depositing and coating inorganic substances on the surface of polyimide nanofibers, the inorganic in-situ modified polyimide nanofibers obtained can further combine the excellent temperature resistance and wettability of polyimide nanofibers and inorganic substances, so as to realize the preparation of flexible "inorganic ceramic" diaphragms with polyimide nanofibers as the matrix.

[0010] Preferably, in step S1, the aromatic dianhydride is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride or hexafluoro dianhydride;

[0011] The aromatic diamine is at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone or 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether.

[0012] Preferably, in step S1, the monomer further comprises a sulfonated aromatic dicarboxylic acid;

[0013] Preferably, the sulfonated aromatic dicarboxylic acid is at least one of 5-sulfoisophthalic acid, 5-sodium sulfoisophthalic acid, 2-sulfoterephthalic acid, 2-sodium sulfoterephthalic acid, 4-sulfophthalic acid, 4-sodium sulfophthalic acid, 5,8-dicarboxynaphthalene-2-sulfonate, 2,2'-disulfonyl-4,4'-biphenyldicarboxylic acid or 2,2'-disulfonyl-4,4'-biphenyldicarboxylic acid.

[0014] Preferably, the molar ratio of the sulfonated aromatic dicarboxylic acid to the aromatic dianhydride is 0.05-0.3:0.7-0.95.

[0015] In the present invention, sulfonated aromatic dicarboxylic acid is used as a monomer to be polycondensed into a polyamic acid containing a sulfonic acid group, which can form better adsorption and bonding with salt ions in an inorganic precursor salt solution, and finally make the salt ions evenly and effectively attached to the surface of the polyamic acid fiber. After imidization treatment, an effective inorganic coating modification can be formed on the surface of the polyimide fiber, further improving the fiber's temperature resistance, compatibility with ceramics, and improving the performance of the diaphragm.

[0016] Preferably, in step S2, the inorganic precursor salt solution is at least one of aluminum salt, tin salt, titanium salt, zinc salt, magnesium salt or zirconium salt solution;

[0017] Preferably, the solvent of the inorganic precursor salt solution is at least one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone;

[0018] Preferably, the content of the inorganic precursor salt solution is 1-10 wt %.

[0019] Preferably, in step S2, the electrospinning parameters include: spinning voltage of 15-35 kV, spinning temperature of 20-40° C., spinning humidity of 20-60%, receiving distance of 10-30 cm, and pushing rate of 0.5-2 mL / h.

[0020] Preferably, in step S3, the imidization treatment is a thermal imidization treatment;

[0021] Preferably, the thermal imidization parameters include: a heating rate of 5-20° C. / min, a heating temperature of 350-450° C., and a time of 2-4 h.

[0022] The present invention also provides a modified composite diaphragm, the composite diaphragm comprising a polyolefin base film and a high temperature resistant ceramic coating coated on any one side or both sides of the polyolefin base film;

[0023] The high temperature resistant ceramic coating comprises ceramic particles and the polyimide nanofibers according to any one of claims 1 to 6.

[0024] Preferably, the mass ratio of the ceramic particles to the polyimide nanofibers is 100:1-30;

[0025] Preferably, the ceramic particles are at least one of boehmite, aluminum oxide, silicon dioxide, barium titanate, titanium dioxide, zinc oxide, magnesium oxide, magnesium hydroxide or zirconium oxide.

[0026] Preferably, the high temperature resistant ceramic coating further comprises a binder;

[0027] Preferably, the binder is at least one of polyacrylate, polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinyl pyrrolidone or polyvinyl alcohol.

[0028] In the present invention, an innovative electrospinning method is used to prepare inorganic in-situ modified polyimide nanofibers. The nanofibers have the advantages of excellent heat resistance, flexibility, chemical stability, wettability, high porosity and excellent mechanical properties. In addition, the surface of the nanofibers is coated with inorganic substances, which can form effective compatibility with ceramic particles, thereby effectively entangled and coated the ceramic particles, and finally form a coating structure with a more stable structure, thereby further improving the high temperature resistance and battery performance of the obtained diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the polyimide nanofibers in situ modified by inorganic substances as described in Example 1. DETAILED DESCRIPTION

[0030] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0031] Example 1

[0032] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0033] 4,4'-diaminodiphenyl ether is added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, and then pyromellitic anhydride is added, and the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether is 1:1, and stirred under nitrogen protection to react to obtain a polyamic acid spinning stock solution with a content of 15wt%; aluminum chloride hexahydrate is also added to DMF and stirred to mix evenly to obtain an inorganic precursor salt solution with a content of 5wt%; the above inorganic precursor salt solution is added to the above polyamic acid spinning stock solution and stirred to mix evenly, and the six The mass ratio of aluminum chlorohydrate to polyamic acid is 1:6, and electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 25 kV, spinning temperature of 25°C, spinning humidity of 40%, receiving distance of 20 cm, and pushing rate of 1 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 10°C / min, heating temperature of 400°C, and heating time of 3 hours to obtain the inorganic in-situ modified polyimide nanofibers.

[0034] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0035] Aluminum oxide powder (average particle size of 200nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, inorganic in-situ modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0036] Example 2

[0037] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0038] Add p-phenylenediamine to N,N-dimethylformamide (DMF) and stir to dissolve completely, then add 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, the molar ratio of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride to p-phenylenediamine is 1:1, stir and react under nitrogen protection to obtain a polyamic acid spinning stock solution with a content of 15wt%; add stannous chloride dihydrate to DMF and stir and mix uniformly to obtain an inorganic precursor salt solution with a content of 5wt%; add the above inorganic precursor salt solution to the above polyamic acid spinning stock solution and stir and mix uniformly , the mass ratio of stannous chloride dihydrate to polyamic acid is 1:6, and electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 15 kV, spinning temperature of 25 ° C, spinning humidity of 40%, receiving distance of 30 cm, and pushing rate of 0.5 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 20 ° C / min, heating temperature of 350 ° C, and heating time of 4 hours to obtain the inorganic in-situ modified polyimide nanofibers.

[0039] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0040] Aluminum oxide powder (average particle size of 200nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, inorganic in-situ modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0041] Example 3

[0042] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0043] 4,4'-diaminodiphenylmethane was added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, and then 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride was added, and the molar ratio of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride to 4,4'-diaminodiphenylmethane was 1:1, and the reaction was stirred under nitrogen protection to obtain a polyamic acid spinning stock solution with a content of 15wt%; titanium tetrachloride was also added to DMF and stirred to mix evenly to obtain an inorganic precursor salt solution with a content of 5wt%; the above inorganic precursor salt solution was added to the above polyamic acid spinning stock solution; The silk stock solution is stirred and mixed evenly, the mass ratio of titanium tetrachloride and polyamic acid is 1:6, and electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 35 kV, spinning temperature of 25°C, spinning humidity of 40%, receiving distance of 10 cm, and pushing rate of 2 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 5°C / min, heating temperature of 450°C, and heating time of 2h to obtain the inorganic in-situ modified polyimide nanofibers.

[0044] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0045] Titanium dioxide powder (average particle size of 200nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and sodium carboxymethyl cellulose are added to water and stirred and dispersed evenly. The mass ratio of titanium dioxide powder, inorganic in-situ modified polyimide nanofibers and sodium carboxymethyl cellulose is 100:15:5, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0046] Example 4

[0047] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0048] 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether was added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, and then 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride was added, and the molar ratio of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride to 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether was 1:1, and stirred under nitrogen protection to react to obtain a polyamic acid spinning stock solution with a content of 15wt%; zirconium nitrate pentahydrate was also added to DMF and stirred to mix evenly to obtain an inorganic precursor salt solution with a content of 5wt%; the above inorganic precursor The zirconium nitrate pentahydrate solution is added to the polyamic acid spinning stock solution and stirred to mix evenly. The mass ratio of zirconium nitrate pentahydrate to polyamic acid is 1:6. Electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 25 kV, spinning temperature of 25 ° C, spinning humidity of 40%, receiving distance of 20 cm, and pushing rate of 1 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment. The thermal imidization parameters include: heating rate of 10 ° C / min, heating temperature of 400 ° C, and heating time of 3 h to obtain the inorganic in-situ modified polyimide nanofibers.

[0049] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0050] Zirconium dioxide powder (average particle size of 300nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of zirconium dioxide powder, inorganic in-situ modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0051] Example 5

[0052] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0053] 4,4'-diaminodiphenyl ether was added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, then 5-sulfoisophthalic acid was added, followed by pyromellitic anhydride, the molar ratio of pyromellitic anhydride, 5-sulfoisophthalic acid and 4,4'-diaminodiphenyl ether was 0.1:0.9:1, and stirred under nitrogen protection to obtain a polyamic acid spinning stock solution with a content of 15wt%; aluminum chloride hexahydrate was also added to DMF and stirred to mix evenly to obtain an inorganic precursor salt solution with a content of 5wt%; the above inorganic precursor salt solution was added to the above poly The polyamide acid spinning stock solution is stirred and mixed evenly, the mass ratio of aluminum chloride hexahydrate to polyamide acid is 1:6, and electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 25 kV, spinning temperature of 25°C, spinning humidity of 40%, receiving distance of 20 cm, and pushing rate of 1 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 10°C / min, heating temperature of 400°C, and heating time of 3 hours to obtain the inorganic in-situ modified polyimide nanofibers.

[0054] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0055] Aluminum oxide powder (average particle size of 200nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, inorganic in-situ modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0056] Example 6

[0057] This embodiment provides an inorganic in-situ modified polyimide nanofiber, which is prepared by the following method:

[0058] 4,4'-diaminodiphenyl ether is added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, then 5-sulfoisophthalic acid is added, followed by pyromellitic anhydride, the molar ratio of pyromellitic anhydride, 5-sulfoisophthalic acid and 4,4'-diaminodiphenyl ether is 0.2:0.8:1, and stirred under nitrogen protection to obtain a polyamic acid spinning solution with a content of 15wt%; aluminum chloride hexahydrate is also added to DMF and stirred to mix evenly to obtain an inorganic precursor salt solution with a content of 5wt%; the above inorganic precursor salt solution is added to the above poly The polyamide acid spinning stock solution is stirred and mixed evenly, the mass ratio of aluminum chloride hexahydrate to polyamide acid is 1:6, and electrospinning is performed by a needle electrospinning method. The electrospinning parameters include: spinning voltage of 25 kV, spinning temperature of 25°C, spinning humidity of 40%, receiving distance of 20 cm, and pushing rate of 1 mL / h to obtain precursor fibers; the precursor fibers are subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 10°C / min, heating temperature of 400°C, and heating time of 3 hours to obtain the inorganic in-situ modified polyimide nanofibers.

[0059] This embodiment also provides a modified composite diaphragm, which is prepared by the following method:

[0060] Aluminum oxide powder (average particle size of 200nm), the above-mentioned inorganic in-situ modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, inorganic in-situ modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a high-temperature resistant ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0061] Comparative Example 1

[0062] This comparative example proposes a polyimide nanofiber, which is prepared by the following method:

[0063] 4,4'-diaminodiphenyl ether is added into N,N-dimethylformamide (DMF) and stirred to be completely dissolved, and then pyromellitic anhydride is added, the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether is 1:1, and the reaction is stirred under nitrogen protection to obtain a polyamic acid spinning solution with a content of 15wt%, and electrospinning is performed by a needle electrospinning method, and the electrospinning parameters include: spinning voltage of 25kV, spinning temperature of 25°C, spinning humidity of 40%, receiving distance of 20cm, and pushing rate of 1mL / h to obtain a precursor fiber; the precursor fiber is subjected to thermal imidization treatment, and the thermal imidization parameters include: heating rate of 10°C / min, heating temperature of 400°C, and heating time of 3h to obtain the polyimide nanofiber.

[0064] This comparative example also proposes a modified composite diaphragm, which is prepared by the following method:

[0065] Aluminum oxide powder (average particle size of 200 nm), the above-mentioned polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0066] Comparative Example 2

[0067] This comparative example proposes a modified polyimide nanofiber, which is prepared by the following method:

[0068] 4,4'-diaminodiphenyl ether was added to N,N-dimethylformamide (DMF) and stirred to dissolve completely, and then pyromellitic anhydride was added, and the molar ratio of pyromellitic anhydride to 4,4'-diaminodiphenyl ether was 1:1, and the reaction was stirred under nitrogen protection to obtain a polyamic acid spinning solution with a content of 15wt%; aluminum oxide powder (average particle size of 200nm) was added to the above polyamic acid spinning solution and stirred to mix evenly, and the mass ratio of aluminum oxide powder to polyamic acid was The ratio of the raw materials to the raw materials is 1:6, and electrospinning is performed by a needle electrospinning method. The parameters of the electrospinning include: a spinning voltage of 25 kV, a spinning temperature of 25°C, a spinning humidity of 40%, a receiving distance of 20 cm, and a pushing rate of 1 mL / h to obtain a precursor fiber; the precursor fiber is subjected to a thermal imidization treatment, and the parameters of the thermal imidization include: a heating rate of 10°C / min, a heating temperature of 400°C, and a heating time of 3 hours to obtain the modified polyimide nanofiber.

[0069] This comparative example also proposes a modified composite diaphragm, which is prepared by the following method:

[0070] Aluminum oxide powder (average particle size of 200nm), the above-mentioned modified polyimide nanofibers and polyacrylate (BYK-381) are added to water and stirred and dispersed evenly. The mass ratio of aluminum oxide powder, modified polyimide nanofibers and polyacrylate is 100:15:3, and a coating slurry with a content of 50wt% is obtained; after vacuum defoaming, the coating slurry is coated on one side surface of a polyethylene diaphragm by gravure coating. The polyethylene diaphragm has a thickness of 12μm and a porosity of 45%. After drying at 60°C, a ceramic coating with a thickness of 4μm is formed, thereby obtaining the modified composite diaphragm.

[0071] Performance Test:

[0072] The modified composite separators obtained in the above examples and comparative examples were tested for mechanical properties, thermal shrinkage and battery performance, and the test results are shown in Table 1.

[0073] Mechanical properties: The tensile properties of the modified composite diaphragm were measured using an electronic universal testing machine at a test temperature of 25°C;

[0074] Thermal shrinkage rate: Cut a 5cm×5cm modified composite diaphragm sample, measure the longitudinal (MD) and transverse (TD) dimensions before baking, and record them as L1 and H1 respectively. Then bake the composite diaphragm at 150℃ for 1h and 200℃ for 1h, and measure the MD and TD dimensions again, and record them as L2 and H2 respectively.

[0075] The MD heat shrinkage is (L1-L2) / L1×100%, and the TD heat shrinkage is (H1-H2) / H1×100%. The higher value of the heat shrinkage in MD and TD is defined as the heat shrinkage of the modified composite separator.

[0076] Battery performance: The modified composite diaphragm is mixed with the positive electrode sheet (lithium cobalt oxide, conductive agent acetylene black, and polyvinylidene fluoride are mixed in N-methylpyrrolidone solvent at a mass ratio of 97:1:2 to form a positive electrode slurry, which is coated on aluminum foil and dried, and then cold pressed and stripped to form a positive electrode sheet), and the negative electrode sheet (graphite, conductive carbon black SuperP, and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 97:1:2 to form a negative electrode slurry, which is coated on copper foil and dried, and then cold pressed and stripped to form a negative electrode sheet). The lithium ion battery was assembled in a conventional manner, and the battery performance was tested. Specifically, the battery was charged to 4.35V at 1C constant current and constant voltage, the battery was cut off at 0.1C, left for 10min, cycled 200 times, and the capacity retention rate was recorded after 200 cycles.

[0077] Table 1 Performance test results of the modified composite membranes described in Examples and Comparative Examples

[0078]

[0079] It can be seen from the above table that compared with Comparative Example 1 and Comparative Example 2, the modified composite diaphragm provided in each embodiment of the present application has better mechanical properties, thermal dimensional stability and battery performance.

[0080] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An inorganic in-situ modified polyimide nanofiber, It is characterized in that The nanofibers are prepared by the following method: S1, polycondensing the monomers of aromatic dianhydride and aromatic diamine to obtain a polyamic acid spinning solution; S2, adding the inorganic precursor salt solution to the polyamic acid spinning stock solution, mixing, and obtaining precursor fibers after electrospinning; S3, subjecting the precursor fiber to imidization treatment to obtain the inorganic in-situ modified polyimide nanofiber.

2. The inorganic in-situ modified polyimide nanofiber according to claim 1, It is characterized in that In step S1, the aromatic dianhydride is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride or hexafluoro dianhydride; The aromatic diamine is at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone or 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether.

3. The inorganic in-situ modified polyimide nanofiber according to claim 1 or 2, It is characterized in that In step S1, the monomer further comprises a sulfonated aromatic dicarboxylic acid; Preferably, the sulfonated aromatic dicarboxylic acid is at least one of 5-sulfoisophthalic acid, 5-sodium sulfoisophthalic acid, 2-sulfoterephthalic acid, 2-sodium sulfoterephthalic acid, 4-sulfophthalic acid, 4-sodium sulfophthalic acid, 5,8-dicarboxynaphthalene-2-sulfonate, 2,2'-disulfonyl-4,4'-biphenyldicarboxylic acid or 2,2'-disulfonyl-4,4'-biphenyldicarboxylic acid. Preferably, the molar ratio of the sulfonated aromatic dicarboxylic acid to the aromatic dianhydride is 0.05-0.3:0.7-0.

95.

4. The inorganic in-situ modified polyimide nanofiber according to any one of claims 1 to 3, It is characterized in that In step S2, the inorganic precursor salt solution is at least one of aluminum salt, tin salt, titanium salt, zinc salt, magnesium salt or zirconium salt solution; Preferably, the solvent of the inorganic precursor salt solution is at least one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; Preferably, the content of the inorganic precursor salt solution is 1-10 wt %.

5. The inorganic in-situ modified polyimide nanofiber according to any one of claims 1 to 4, It is characterized in that In step S2, the electrospinning parameters include: spinning voltage of 15-35 kV, spinning temperature of 20-40°C, spinning humidity of 20-60%, receiving distance of 10-30 cm, and pushing rate of 0.5-2 mL / h.

6. The inorganic in-situ modified polyimide nanofiber according to any one of claims 1 to 5, It is characterized in that In step S3, the imidization treatment is a thermal imidization treatment; Preferably, the thermal imidization parameters include: a heating rate of 5-20° C. / min, a heating temperature of 350-450° C., and a time of 2-4 h.

7. A modified composite diaphragm, It is characterized in that The composite diaphragm comprises a polyolefin base film and a high temperature resistant ceramic coating coated on any one side or both sides of the polyolefin base film; The high temperature resistant ceramic coating comprises ceramic particles and the polyimide nanofibers according to any one of claims 1 to 6.

8. The modified composite diaphragm according to claim 7, It is characterized in that The mass ratio of the ceramic particles to the polyimide nanofibers is 100:1-30; Preferably, the ceramic particles are at least one of boehmite, aluminum oxide, silicon dioxide, barium titanate, titanium dioxide, zinc oxide, magnesium oxide, magnesium hydroxide or zirconium oxide.

9. The modified composite diaphragm according to claim 7 or 8, It is characterized in that The high temperature resistant ceramic coating also includes a binder; Preferably, the binder is at least one of polyacrylate, polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinyl pyrrolidone or polyvinyl alcohol.

10. A lithium ion battery, It is characterized in that comprising a positive electrode, a negative electrode and a separator located between the positive electrode and the negative electrode; The diaphragm is the modified composite diaphragm according to claim 8 or 9.

Citation Information

Patent Citations

  • Polyamide acid dispersion liquid and preparation method thereof as well as polyimide film

    CN103172859A

  • Method for preparing polyimide porous nanofiber electrode diaphragm

    CN104752665A

  • Lithium ion battery composite diaphragm and preparation method thereof

    CN113410580A

  • Preparation method of high-strength weather-resistant polyimide fiber

    CN113622049A

  • Polyimide / zinc oxide composite lithium ion battery diaphragm and preparation method thereof

    CN113725553A